Engineering Challenges for Sustainable Underground Use Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
This volume comprises a set of high-quality, refereed papers that address the different aspects related to the geotechnical and structural design and construction of deep excavations, tunnels and underground space facilities as well as the effect of their construction on the surroundings. The papers cover planning, design, modeling, monitoring and construction aspects of these essential structures. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.